Manajemen kebijakan kepala madrasah dalam meningkatkan mutu pendidikan - Murni Yanto; Irwan Fathurrochman (Indonesian Institute for Counseling, Education and Therapy (IICET), 2019)
This qualitative research raises the theme of Madrasah Head Policy Management in improving the quality of education in Madrasah Ibtidaiyah Negeri 1 Rejang Lebong, the results of the study indicate that the quality of education can be achieved by prioritizing madrasas in curriculum development and teacher professional development through the activities of Teacher Working Groups, Madrasah Head Policy Management can be done through internal and external factors of madrasas in fostering teacher honesty, appreciation, harmonious and humane climate of communication of democracy between leaders and teachers, Principals of madrasas foster a conducive atmosphere of madrasas, foster a sense of responsibility to teachers in teaching, through coordination with district leaders, madrasa committee and the community, so that the quality of education can be improved.